Cancer Immunotherapy and CAR T Cells - King S Ong; Zack ST. Lim; Boenjamin Setiawan (PT Kalbe Farma Tbk., 2018)
Within the past decade, radical changes of idea emerged from the works of research scientists, medical experts, and oncologists. Instead of treating cancers with man-made chemicals or chemotherapy and radiotherapy, or surgically remove the tumor, we should unleash the power of our own body immune system. Indeed, such approach has borne fruits and benefited at least for some cancer patients. This review describes various types of immunotherapy known to date, with its beneficial effects, albeit some with serious harmful effects. To understand how immunotherapies work, we also review some biologic characteristics of cancer cells that let them evade attacks from our immune system; cancer microenvironment that works in favor or protecting the growth of cancer against our immune system will also be discussed. Hanya dalam jangka 10 tahun terakhir, telah terjadi perubahan radikal hasil penelitian para ahli, ahli medis, dan ahli onkologi. Di samping cara klasik penyembuhan kanker seperti obat-obat kimia sintetik atau kemoterapi dan radioterapi atau pembedahan, kini para ahli telah menggunakan sistem imunitas tubuh penderita sendiri. Cara ini telah terbukti dalam pengobatan beberapa pasien kanker. Dalam ulasan ini kami akan memaparkan beberapa immunoterapi saat ini dengan hasil baik meskipun masih terdapat beberapa efek samping berbahaya. Untuk memahami bagaimana imunoterapi bekerja, akan diulas dan dijelaskan sifat-sifat biologi sel kanker, dan bagaimana kanker sel bisa menghindari serangan sistem imun; dan lingkungan mikrokanker (cancer microenviroment) yang melindungi kanker dari sistem imun.